Behavior as a resourceessential self-regulation of psyche - Кочарян, Ігор Олександрович (Psychological Counseling and Psychotherapy)
The article is devoted to functioning of executive component of self-regulation system, which ensure the implementation of self-actualizing tendencies. Certain behavioral patterns are offered as a resource essential self-regulation of the psyche. These patterns are designed to fulfill a number of conditions for the recognition and follow the messages intrapsychic instance "essential Self": self-esteem, effectiveness and appreciation. Following J. Stevens describes seven behavior patterns that allow a person to maintain these conditions. To ensure these conditions must be a system of two behavioral patterns, one of which performs the function of expansive, and the other - a deterrent. Self-esteem (dignity) is provided with pride and humility; effectiveness - the courage and endurance; gratitude - a taste for life and self-sacrifice; and perseverance is able to back up each of the necessary conditions. The psychotherapeutic setting the above seven behavioral patterns necessary for the implementation of the human self-actualizing tendencies.